1989
DOI: 10.1002/em.2850130311
|View full text |Cite
|
Sign up to set email alerts
|

Testing of sunset yellow and orange II for genotoxicity in different laboratory animal species

Abstract: The azo dyes Sunset Yellow and Orange II were gavaged to rodent species to check bile, urine, and fecal extracts for possible mutagenic activity in the Ames test or in bone marrow cells for clastogenicity using cytogenetic test systems. After oral application the dyes showed a negative response in bile, excrements, and bone marrow. When an exogenous metabolic activation was performed, increased revertant numbers using Salmonella strain TA100 were obtained only in fecal extracts of Sunset Yellow-treated animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The metabolites were monitored in the faeces using HPLC and reported to be non-genotoxic as well. The results of these studies agrees with that of Wever et al (1989) who did not find any mutagenicity or clastogenicity effects when the dye was administered to rodents by gavage.…”
Section: In Vivo Testingsupporting
confidence: 90%
See 1 more Smart Citation
“…The metabolites were monitored in the faeces using HPLC and reported to be non-genotoxic as well. The results of these studies agrees with that of Wever et al (1989) who did not find any mutagenicity or clastogenicity effects when the dye was administered to rodents by gavage.…”
Section: In Vivo Testingsupporting
confidence: 90%
“…They also justified the use of the intra-peritoneal route on the poor uptake of allura red from the intestine and suggested that this coupled with the possibility of microbial formation of substances with local cellular action might partly explain the toxicity seen in the report by Shimada et al (2010). Early reports demonstrated the non-mutagenicity of sunset yellow on E. coli, four tester strains of S. typhimurium TA 1538, 1535, 100 and 98 strains with or without metabolic activation (Chung et al, 1981;JECFA, 1982;Wever et al, 1989). Haveland-Smith and Combes (1980), also tested the ability of twenty five dyes to induce mutations in a tryptophan-requiring E. coli strain (sensitive to base substitutions) and a histidine auxotroph of S. typhimurium strain TA1538 (specific for frameshifts).…”
Section: In Vivo Assaysmentioning
confidence: 99%
“…It was concluded by the authors that no genotoxic harm is to be expected from the ingestion of Sunset Yellow FCF (Wever et al, 1989). It was concluded by the authors that no genotoxic harm is to be expected from the ingestion of Sunset Yellow FCF (Wever et al, 1989).…”
Section: Genotoxicitymentioning
confidence: 97%
“…Sunset Yellow FCF was administered to rodent species by gavage to check for possible mutagenic activity in the Ames test, or for clastogenicity in bone marrow cells using cytogenetic test systems. It was concluded by the authors that no genotoxic harm is to be expected from the ingestion of Sunset Yellow FCF (Wever et al, 1989). EFSA Journal 2009; 7(11):1330 Mice orally exposed to 0.17 or 1.7 mg/kg bw of Sunset Yellow FCF did not display any increase in the number of cells with chromosomal damages (Durnev et al, 1995).…”
Section: Genotoxicitymentioning
confidence: 99%
“…Negative results were also obtained in tests with the chemically reduced component amines of three of the dyes (Allura Red AC, Amaranth and Tartrazine), both in presence and absence of exogenous metabolic activation. Some positive findings have been observed in some in vitro tests with extracts from or rat metabolites of Allura Red AC, Amaranth and Sunset Yellow FCF (Henschler et al, 1985;Münzner and Wever, 1987;Prival et al, 1988;Wever et al, 1989).…”
Section: Discussionmentioning
confidence: 97%